STRATEGI PROTEKSI EKONOMI PASAR SAMPANG DALAM MENGHADAPI MONOPOLI DENGAN PRAKTIK KOLABORASI - Darwanto, Agus; Lestari, Dwi; Nurhidayah, Okti (Universitas Negeri Surabaya, 2022)
Sampang District is the only area in Cilacap Regency where citizens of Chinese descent are not allowed to have their own business to protect native traders from the monopoly of citizens of Chinese descent. The purpose of this study was to determine the trade protection model applied by Sampang residents in dealing with trade monopoly efforts from residents of Chinese descent. The research methodology used is the mix method. Collecting data by conducting surveys, observations, and interviews. The research location is Sampang District. Withdrawal of samples using purposive sampling method by interviewing people who know the trading system that applies in Sampang District. Analysis and processing of data using descriptive analysis. The results of the study show that the non-involvement of citizens of Chinese descent in the Sampang economy has been going on for a long time, namely when Sampang residents tried to protect their territory from the direct involvement of citizens of Chinese descent in economic activities. Sampang residents allow a business collaboration system between residents of Chinese descent and indigenous residents but using the names of indigenous people. With this strategy, the people of Sampang can develop the economy of the indigenous people without being dependent on people of Chinese descent.